Description of Complementary Feeding and Weight Gain in Infants Aged 6-24 Months at Tenggaba Health Center - Aproditus Lende Mere; Utma Aspatria; Anna Henny Talahatu (Universitas Nusa Cendana, 2022)
Malnutrition is a common health problem. One of the causes is the provision of MP-ASI that is not following the age and needs of the baby. This study aims to determine the description of complementary feeding and infant weight gain (MP-ASI). This research is descriptive research with a quantitative approach. Data collection was carried out from October-November 2020. The study population was 90 mothers. The sample size is 73 mothers who have babies aged 6-24 months. The sampling method used is simple random sampling. The results showed that most of the mothers of children under five were young, ranging from 20-35 years (67.12%), had low education (52.05%), and worked as farmers (76.71%). Family income is low (53.42%). Mother's knowledge about MP-ASI is still lacking (52.06%). Infants who received MP-ASI <6 months was 63.02%. The type of MP-ASI, the frequency of MP-ASI, and the form of MP-ASI were not following the needs of infants aged 6-24 months, 63.02%, 53.42%, and 54.79%, respectively. The level of energy and protein adequacy in infants is included in the less category, respectively 71.23% and 64.39%. The baby's weight gain was in the non-increased category, which was 60.27%. The active role of health workers is needed to provide counseling on the correct way of giving MP-ASI. Mothers also need to be more active in seeking information on how to give MP-ASI and actively participate in posyandu (integrated health post) so that mothers can give MP-ASI to babies according to the age of 6-24 months.